Does it pay to be beautiful? - Eva Sierminska (IZA World of Labor, 2015)
It is a well-established view amongst economists that good-looking people have a better chance of employment and can earn more than those who are less physically attractive. A “beauty premium” is particularly apparent in jobs where there is a productivity gain associated with good looks, though this is different for women and men, and varies across countries. People also sort into occupations according to the relative returns to their physical characteristics; good-looking people take jobs where physical appearance is deemed important while less-attractive people steer away from them, or they are required to be more productive for the same wage.
Keywords: D31; J24; J30; J70; 330; beauty premium; wages; discrimination; gender differentials; occupational sorting; physical attractiveness